2016
DOI: 10.7589/2015-03-063
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antibodies to Selected Viruses and Parasites in Introduced and Endemic Carnivores in Western Madagascar

Abstract: Introduced animals impact endemic populations through predation, competition, and disease transmission. Populations of endemic carnivores in Madagascar are declining, and pathogens transmitted from introduced species may further endanger these unique species. We assessed the exposure of introduced and endemic carnivores to common viral and parasitic pathogens in two national parks of Madagascar (Kirindy Mitea National Park and Ankarafantsika National Park) and their neighboring villages. We also identified var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Sex was an important variable only for the prevalence of FPLV. This effect of sex on feline viral diseases has been explored for lion, cheetahs ( Acinonyx jubatus ), wildcat and sand cat ( Felis margarita ), although no clear relationship emerged (Hoffman-Lehmann et al 1996 ; Ostrowski et al 2003 ; Munson et al 2004 ; Pomerantz et al 2016 ). The only felid with clear effects of sex on pathogen infection was cheetah, where FHV was higher for males and FCV higher for females, although these results were not based on robust statistical analysis (Munson et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sex was an important variable only for the prevalence of FPLV. This effect of sex on feline viral diseases has been explored for lion, cheetahs ( Acinonyx jubatus ), wildcat and sand cat ( Felis margarita ), although no clear relationship emerged (Hoffman-Lehmann et al 1996 ; Ostrowski et al 2003 ; Munson et al 2004 ; Pomerantz et al 2016 ). The only felid with clear effects of sex on pathogen infection was cheetah, where FHV was higher for males and FCV higher for females, although these results were not based on robust statistical analysis (Munson et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…The high occupancy of free-ranging cats and dogs in the landscape indicates considerable competition with fosas through the consumption of shared prey (Brockman et al, 2008) and exclusion from habitat. The spread of disease, such as toxoplasmosis (Pomerantz et al, 2016; Rasambainarivo et al, 2017), between exotic species, fosas and their prey is of concern, potentially imperilling the health of the fosa population in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…Fatal cases of Toxoplasma gondii infection have been recorded in captive fosas (Corpa et al, 2013) and lemurs (Juan-Sallés et al, 2011; Siskos et al, 2015), highlighting their vulnerability to lethal infections. Field studies of exotic carnivores in Ankarafantsika National Park have identified the occurrence of multiple viruses and parasites, including canine parovirus, feline calicivirus and T. gondii (Pomerantz et al, 2016), the latter prevalent in > 93% of captured wild fosas. The detrimental impact of disease on Madagascar's wild fosa populations could be significant, reflecting disease-related species population declines elsewhere (Pedersen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Fosas are categorized as Vulnerable on the IUCN Red List of Threatened Species, for a combination of reasons (Hawkins, 2016). These include low population densities compared to other tropical carnivores (Rahajanirina, 2003; Hawkins & Racey, 2005), country-wide loss of forested habitats (Gerber et al, 2012; Kotschwar Logan et al, 2015), and the introduction of other carnivore species that compete for prey and transmit diseases to fosas (Farris et al, 2015b; Pomerantz et al, 2016). Fosas are also subject to intense persecution because they are widely believed to prey on domestic animals, particularly poultry (Woodroffe & Ginsberg, 1998; García & Goodman, 2003; Golden, 2009; Kotschwar Logan et al, 2015; Farris et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%